2011
DOI: 10.1037/a0025690
|View full text |Cite
|
Sign up to set email alerts
|

Les pratiques parentales des parents d'enfants en difficultés de comportement: Effets de la dyade parent-enfant.

Abstract: Cette étude a pour objectif d'identifier les différences et les similitudes entre les pratiques parentales du père et de la mère d'enfants de maternelle identifiés comme manifestant des difficultés de comportement (n = 109), selon que l'on est en présence de parents de garçons ou de parents de filles. À partir de mesures autorévélées des pratiques parentales et d'une observation directe des dyades parent-enfant en situation de jeu, les résultats indiquent plus de complicité durant une interaction de jeu chez l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
1
1
Order By: Relevance
“…Our findings stand in contrast to those from previous studies, which found self‐reported autonomy support and control to be negatively correlated (e.g. Annear & Yates, 2010; Besnard, Verlaan, Capuano, Poulin, & Vitaro, 2011). These contrasting findings could result from differences in sampling (ours did not include “at‐risk” students nor elementary school children) but also in measurement.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings stand in contrast to those from previous studies, which found self‐reported autonomy support and control to be negatively correlated (e.g. Annear & Yates, 2010; Besnard, Verlaan, Capuano, Poulin, & Vitaro, 2011). These contrasting findings could result from differences in sampling (ours did not include “at‐risk” students nor elementary school children) but also in measurement.…”
Section: Discussioncontrasting
confidence: 99%
“…First, few tools have been specifically developed to assess paternal parenting practices; their lack of refinement in this regard may unduly influence their assessment of fathers (Pettit, Bates, & Dodge, 1993). Furthermore, little is known about father-specific dimensions associated with CBP whereas those specific to mothers are more established (Besnard, Verlaan, Capuano, Poulin, & Vitaro, 2011). Second, results may be accounted for by the different tasks for fathers and mothers.…”
Section: Discussionmentioning
confidence: 99%